2006
DOI: 10.1038/sj.onc.1209757
|View full text |Cite
|
Sign up to set email alerts
|

Progestin-induced caveolin-1 expression mediates breast cancer cell proliferation

Abstract: Progestin regulation of gene expression was assessed in the progestin-dependent murine tumor line C4HD which requires MPA, a synthetic progestin, for in vivo growth and expresses high levels of progesterone receptor (PR). By using suppressive subtractive hybridization, caveolin-1 was identified as a gene whose expression was increased with in vivo MPA treatment. By Northern and Western blot analysis, we further confirmed that caveolin-1 mRNA and protein expression increased in MPA-treated tumors as compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 65 publications
1
33
0
Order By: Relevance
“…Caveolin-1 functions as a molecular switch for some of the extranuclear actions of sex steroids, and progesterone is able to regulate this protein (Salatino et al 2006, Sotgia et al 2006. It would thus be interesting to clarify the role of caveolin-1 in progesterone-associated breast cancer cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Caveolin-1 functions as a molecular switch for some of the extranuclear actions of sex steroids, and progesterone is able to regulate this protein (Salatino et al 2006, Sotgia et al 2006. It would thus be interesting to clarify the role of caveolin-1 in progesterone-associated breast cancer cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Separately, several groups have demonstrated that P induces the expression and phosphorylation of STAT3 and STAT5 (Richer et al 1998, Proietti et al 2005, where P-induced activation of Jak1 and Jak2 and phosphorylation of STAT1 and STAT3 is Src dependent (Zhang et al 2000, Proietti et al 2005. More recently, c-Src was shown to phosphorylate P-induced caveolin-1 that mediates a proliferative effect of P on mammary tumor cells (Salatino et al 2006). Although several groups have implicated the MAP and PI3 kinases as downstream effectors of crosstalk between PR and c-Src (Lange 2004), our present results indicate that these pathways do not participate in the synergistic effect of PC PRL on the MMTV-LTR.…”
Section: Discussionmentioning
confidence: 99%
“…This antibody has been used and validated previously by our group and by others. 21,23,24 Sections were incubated with LSAB2 (Dakocytomation). 3-3 0 -diaminobenzidine was used for colour development and haematoxylin was used for counterstaining.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%